2008
DOI: 10.3844/ajabssp.2008.502.510
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Aloe Vera Leaf Gel: A Review

Abstract: Proper scientific investigations on Aloe vera have gained more attention over the last decade due to its reputable, medicinal, pharmaceutical and food properties. Some publications have appeared in reputable scientific journals that have made appreciable contributions to the discovery of the functions and utilizations of Aloe vera lacking processing of leaf gel. Present processing techniques aims at producing best quality aloe products but end aloe products contain very little or virtually no active ingredient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 19 publications
(13 reference statements)
1
118
0
13
Order By: Relevance
“…A few examples of product applications for food and beverage products are aloe soft drink (with electrolytes), diet drink with soluble fiber, hangover drink, healthy vegetable juice, tropical fruit juice with Aloe vera, yogurt and yogurt drinks, Aloe vera jelly desserts with chunks of aloe, instant Aloe vera granules, Aloe vera gums for sore or bleeding gums, Aloe vera candy, Aloe vera sorbet with citrus juice and Aloe vera smoothies (Ramachandra and Rao 2008). Now, the processing of Aloe vera gel, derived from the leaf pulp of the plant, has become a big industry worldwide due to application in food industry.…”
Section: Introductionmentioning
confidence: 99%
“…A few examples of product applications for food and beverage products are aloe soft drink (with electrolytes), diet drink with soluble fiber, hangover drink, healthy vegetable juice, tropical fruit juice with Aloe vera, yogurt and yogurt drinks, Aloe vera jelly desserts with chunks of aloe, instant Aloe vera granules, Aloe vera gums for sore or bleeding gums, Aloe vera candy, Aloe vera sorbet with citrus juice and Aloe vera smoothies (Ramachandra and Rao 2008). Now, the processing of Aloe vera gel, derived from the leaf pulp of the plant, has become a big industry worldwide due to application in food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Aloe vera gel is widely used in cosmetics and toiletries for its moisturizing and revitalizing action [22,23]. The whole leaf of Aloe vera is known to aid cellular repair as well as digestion, assimilation of foods, vitamins, minerals and other vital nutrients to rejuvenate the skin [24]. The fresh gel, juice or formulated products have been used for medical and cosmetic purposes and to enhance general health [25].…”
Section: Aloe Veramentioning
confidence: 99%
“…Other important factors for biological activities concern extraction technique, processing and storage conditions, the leaf portion considered and the stage of development and the health status of the plants (Amruta & Purushottam 2007;Romani et al 2008;Pellizzoni et al 2012). In particular, Aloe leaves are reported to lose their biological activity starting from 6 h after harvest at room temperature starting (Ramachandra & Srinivasa Rao 2008). The age of the plants plays an important role: Hu et al (2003) reported that leaves from three years old Aloe barbadensis plants contained significantly higher levels of polysaccharides and flavonoids than leaves of two and four years old plants.…”
Section: Introductionmentioning
confidence: 99%